2020
DOI: 10.3389/fnins.2020.00528
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on the Use of Haptic Feedback for Brain-Computer Interfaces and Neurofeedback

Abstract: Neurofeedback (NF) and brain-computer interface (BCI) applications rely on the registration and real-time feedback of individual patterns of brain activity with the aim of achieving self-regulation of specific neural substrates or control of external devices. These approaches have historically employed visual stimuli. However, in some cases vision is unsuitable or inadequately engaging. Other sensory modalities, such as auditory or haptic feedback have been explored, and multisensory stimulation is expected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 111 publications
1
38
0
Order By: Relevance
“…Numerous research studies have been led to assess the efficiency of providing feedback through other modalities than the visual one, i.e. auditory feedback [72], proprioceptive feedback [189,285] or vibrotactile feedback [55,172,247].…”
Section: Feedback Modalitymentioning
confidence: 99%
“…Numerous research studies have been led to assess the efficiency of providing feedback through other modalities than the visual one, i.e. auditory feedback [72], proprioceptive feedback [189,285] or vibrotactile feedback [55,172,247].…”
Section: Feedback Modalitymentioning
confidence: 99%
“…Regarding the type of feedback provided to the user, in other words, the different modalities provided by the BCI system (visual, auditory, and haptic [ 50 ]) from which the subject perceives sensations, it was shown that eight of the proposed works was based exclusively on visual feedback, six on combined visual and auditory feedback, two on haptic and visual feedback, and two implemented visual, auditory, and haptic feedback.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to robotic devices, vibrotactile interfaces with proprioceptive feedback functions are more comfortable, affordable, portable, cheaper and easier to implement. However, up until now, vibrotactile feedback has been scarcely explored in BCI-based NF training applications (for a recent review see [43]). The pioneering studies on this type of haptic feedback were conducted by Chatterjee et al [44] and Cincotti et al [17].…”
Section: Introductionmentioning
confidence: 99%